2020
DOI: 10.1016/j.celrep.2020.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Facilitated Aggregation of Thermo-Sensitive Proteins Shields Them from Degradation during Heat Stress

Abstract: Graphical Abstract Highlights d Misfolded proteins collapse into protein aggregate centers (PACs) upon heat shock d PAC formation requires the Hsp40 chaperone Mas5 d PACs serve as seed for the nucleation of stress granules at severe temperatures d The fate of PACs is refolding, as they protect misfolded proteins from degradation SUMMARY Cells have developed protein quality-control strategies to manage the accumulation of misfolded substrates during heat stress. Using a soluble reporter of misfolding in fission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…98.1% (98.1% ± 2%, n = 185) of wild-type cells and 95.8% (95.8% ± 2.3%, n = 241) of hsp104D cells assembled NuRs upon HS; however, during the recovery, the absence of Hsp104 resulted in a strong delay in NuRs dissolution ( Figure 4D). hsp104D cells also delayed cytoplasmic SG dissolution ( Figure 4D), in agreement with a recent report (Cabrera et al, 2020). Consistently, the absence of Hsp104 resulted in a delay in cell growth recovery after the HS and in a significant decline in cell survival ( Figure 4D).…”
Section: Hsf1 and Hsp104 Are Required For Proper Nur Dissolutionsupporting
confidence: 91%
See 3 more Smart Citations
“…98.1% (98.1% ± 2%, n = 185) of wild-type cells and 95.8% (95.8% ± 2.3%, n = 241) of hsp104D cells assembled NuRs upon HS; however, during the recovery, the absence of Hsp104 resulted in a strong delay in NuRs dissolution ( Figure 4D). hsp104D cells also delayed cytoplasmic SG dissolution ( Figure 4D), in agreement with a recent report (Cabrera et al, 2020). Consistently, the absence of Hsp104 resulted in a delay in cell growth recovery after the HS and in a significant decline in cell survival ( Figure 4D).…”
Section: Hsf1 and Hsp104 Are Required For Proper Nur Dissolutionsupporting
confidence: 91%
“…Although increased protein synthesis and turnover, as well as protection by molecular chaperones, predominate during mild HS, protein aggregation that stops translation and ceases cell growth has a prominent role during extreme conditions (Cabrera et al, 2020;M€ uhlhofer et al, 2019;Wallace et al, 2015). In S. pombe under mild HS (37 C), Hsp70/40 chaperones facilitate the aggregation of non-terminally unfolded proteins in cytosolic PACs, which might serve as nucleation sites for SGs formed at extreme temperatures (Cabrera et al, 2020). Here, we show that during acute HS, several nuclear proteins aggregate and immobilize in a reversible manner at the nucleolar region ( Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with a previous study showing that proteins initially form small amorphous stress foci, and then depend on Hsp104 to remodel these smaller aggregates into larger inclusions (Spokoini et al, 2012). In addition, a recent study in fission yeast found that chaperone-mediated sequestration of misfolded proteins into protein aggregate centres (PACs) protected proteins from degradation and allowed for subsequent refolding (Cabrera et al, 2020). Hence, without Hsp104, ASPA C152W fails to undergo refolding-linked disaggregation and is routed by parallel pathways to degradation or remains in the smaller inclusions.…”
Section: The Yeast Disaggregase Hsp104 Promotes Solubilisation Of Aspsupporting
confidence: 92%